Fundamentals of Entrepreneurship (ENT300) : Pakaian Hari Hari / Nurul Izzah Mohamad Elly … [et al.] - Mohamad Elly, Nurul Izzah; Was, Nur Azlin; Jamal, Nurhaliza; Ahmad Nizam, Nur Ernaniza; Zinal Abidin, Nur Fatin Qirana (2019)
We interviewed one of the Pusat Pakaian Hari Hari staff, named Miss Porinna who has worked there for 5 years and she is now an assistant of the store. She mentioned that the store has been opened for 6 years and a half. Pusat Pakaian Hari Hari first owner is called Teoh Tech Wan. He is a fully chinese man but he's into the practices of Malay culture. She also mentioned that the owner has "a bit of Malay” in him which made him to opened up the famous Pusat Pakaian Hari Hari store. It is a good move of him to open up a clothing store that practices Malay culture because Pusat Pakaian Hari Hari has successfully opened 86 branches in Malaysia excluding Sabah. The Headquarter of the store is located at Selangor and they are planning to open up a new store in Bintulu.